Curcumin suppresses doxorubicin-induced cardiomyocyte pyroptosis via a PI3K/Akt/mTOR-dependent manner - Yu, Wei; Qin, Xing; Zhang, Yuchen; Qiu, Peng; Wang, Linge; Zha, Wenliang; Ren, Jun (Cardiovascular diagnosis and therapy, 2020)
Doxorubicin (DOX) is one of the most effective anti-neoplastic drugs although its clinical use is limited by the severe cardiotoxicity. Apoptosis and defective autophagy are believed to contribute to DOX-induced cardiotoxicity. Here we explored the effect of curcumin (Cur) on DOX-induced cardiac injury and the mechanism involved with a focus on oxidative stress, autophagy and pyroptosis. Kunming mice were challenged with DOX (3 mg·kg , i.p. every other day) with cohorts of mice receiving Cur at 50, 100, 200 and 400 mg·kg via gavage daily. Serum levels of cardiac enzymes, such as aspartate amino transferase (AST), lactate dehydrogenase (LDH), creatine kinase (CK), and heart homogenate oxidative stress markers, such as superoxide dismutase (SOD) and malondialdehyde (MDA) were determined. Echocardiographic and cardiac contraction were examined. Apoptosis, pyroptosis, autophagy and Akt/mTOR-signalling proteins were detected using western blot or electron microscopy. Cardiac contractile properties were assessed including peak shortening, maximal velocity of shortening/relengthening (± dL/dt), time-to-PS, and time-to-90% relengthening (TR90). Superoxide levels were evaluated using DHE staining. GFP-LC3 was conducted to measure autophagosomes. Our study showed that Cur protected against cardiotoxicity manifested by a significant decrease in serum myocardial enzymes and improvement of anti-oxidative capacity. Cur inhibited autophagy and offered overt benefit for cardiomyocyte survive against DOX-induced toxicity. Cur attenuated DOX-induced cardiomyocyte pyroptosis as evidenced by NLR family pyrin domain containing 3 (NLRP3), Caspase-1, and interleukin-18 levels. DOX impaired cardiac function (reduced fractional shortening, ejection fraction, increased plasma cTnI level and TR90, decreased PS and ± dL/dt), the effects of which were overtly reconciled by 100 mg·kg but not 50 mg·kg Cur. H9c2 cells exposure to DOX displayed increased intracellular reactive oxygen species (ROS) and autophagy, the effects of which were nullified by Cur. Autophagy activator rapamycin cancelled off Cur-induced protective effects. Our finding suggested that Cur rescued against DOX-induced cardiac injury probably through regulation of autophagy and pyroptosis in a mTOR-dependent manner.